2008
DOI: 10.1021/np800287n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microbial Community and Polyketide Biosynthetic Potential in the Palmerolide-Producing Tunicate Synoicum adareanum

Abstract: Palmerolide A (1) is a macrolide isolated from the Antarctic tunicate Synoicum adareanum that is of interest due to its potential as an antimelanoma drug. Biosynthesis is predicted to occur via a hybrid PKS-NRPS pathway within S. adareanum, but the identity of the palmerolide-producing organism (host or putative host-associated microorganism) has not been established. Microscopic observation revealed a dense microbial community inside the tunicate, and evidence from 16S rRNA gene DGGE profiles and clone librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 78 publications
4
57
0
Order By: Relevance
“…Bacteria were observed throughout the tunic in all specimens of the Woods Hole C. intestinalis population that we examined (multiple individuals across both summer and winter collections). Similarly dense intratunic bacteria are commonly observed in colonial tunicates, including the Synoicum adareanum and Lissoclinum patella (Riesenfeld et al, 2008;Donia et al, 2011). Although the C. intestinalis specimens used in this study appeared to be healthy adults and the bacteria were observed spread evenly throughout the tunic tissue, we cannot completely discount the possibility that the observed tunic bacteria represent a pathogenic infection.…”
Section: Discussionmentioning
confidence: 67%
“…Bacteria were observed throughout the tunic in all specimens of the Woods Hole C. intestinalis population that we examined (multiple individuals across both summer and winter collections). Similarly dense intratunic bacteria are commonly observed in colonial tunicates, including the Synoicum adareanum and Lissoclinum patella (Riesenfeld et al, 2008;Donia et al, 2011). Although the C. intestinalis specimens used in this study appeared to be healthy adults and the bacteria were observed spread evenly throughout the tunic tissue, we cannot completely discount the possibility that the observed tunic bacteria represent a pathogenic infection.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, Riesenfeld et al found an abundance of proteobacterial 16S sequences and trans-AT PKS genes in an Antarctic didemnid ascidian (80). This ascidian also contained palmerolide, a polyketide with some biosynthetic similarity to patellazoles and a diverse array of other ascidian polyketides.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudovibrio isolates originated from marine invertebrates such as tunicates (Sertan-de Guzman et al, 2007; Riesenfeld, Murray & Baker, 2008), corals (Rypien, Ward & Azam, 2010) and sponges showed antimicrobial activity (Santos et al, 2010; O’ Halloran et al, 2011). Pseudovibrio isolates from corals have antagonist effect against V. coralliilyticus (Rypien, Ward & Azam, 2010).…”
Section: Discussionmentioning
confidence: 99%